2011
DOI: 10.3390/fi3040204
|View full text |Cite
|
Sign up to set email alerts
|

Tool or Toy? Virtual Globes in Landscape Planning

Abstract: Virtual globes, i.e., geobrowsers that integrate multi-scale and temporal data from various sources and are based on a globe metaphor, have developed into serious tools that practitioners and various stakeholders in landscape and community planning have started using. Although these tools originate from Geographic Information Systems (GIS), they have become a different, potentially interactive and public tool set, with their own specific limitations and new opportunities. Expectations regarding their utility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The Local Climate Change Visioning Project (LCCVP), an extensive research endeavour in the community of Delta, BC (Sheppard et al, 2008), was the point of departure for the new game initiative, Future Delta. The 3D photographic visualizations of the LCCVP were remodelled, animated and extended within the interactive game environment of Future Delta (Schroth et al, 2011). and in-depth qualitative interviews with experts about their perception of the imagery in the game as well as asking about overall understanding, learning and motivation in relation to local climate change issues.…”
Section: The Existing Iconography Of Climate Changementioning
confidence: 99%
“…The Local Climate Change Visioning Project (LCCVP), an extensive research endeavour in the community of Delta, BC (Sheppard et al, 2008), was the point of departure for the new game initiative, Future Delta. The 3D photographic visualizations of the LCCVP were remodelled, animated and extended within the interactive game environment of Future Delta (Schroth et al, 2011). and in-depth qualitative interviews with experts about their perception of the imagery in the game as well as asking about overall understanding, learning and motivation in relation to local climate change issues.…”
Section: The Existing Iconography Of Climate Changementioning
confidence: 99%
“…Over the past two decades, virtual globes have become a standard way to integrate, visualize, and analyze multidisciplinary geospatial information at both local and planetary scales [1][2][3][4][5][6]. A number of sophisticated and powerful virtual globes, such as Google Earth [7], NASA World Wind [8], Cesium [9], and other online Earth browsers, have been developed and, subsequently, accepted by Earth scientists from different subject fields as convenient platforms to conduct studies, exchange ideas, present results, and share knowledge with a global perspective in a natural and intuitive way [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The primary reason for virtual globes' success is that they provide more than just a digital replica of the Earth's surface with high-resolution images and terrain data.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual globes are easily accessible, and allow users to effectively create 3D visualizations of various types of spatial data (Bleisch and Nebiker, 2008;Schroth et al, 2011). However, not all these visualizations are successful which can be attributed to the lack of guidelines for creating effective representation.…”
Section: Cognition and 3d Modelsmentioning
confidence: 99%
“…However, not all these visualizations are successful which can be attributed to the lack of guidelines for creating effective representation. Schroth et al, (2011) investigated the usefulness of virtual globes as an interactive community engagement tool for landscape planning, specifically focused on 3D modelling of climate change vulnerability. After stakeholder interviews and questionnaires, Schroth et al found that 3D models portrayed in a virtual globe were a great tool to provide access to spatial data and to raise awareness for the specific project.…”
Section: Cognition and 3d Modelsmentioning
confidence: 99%